2019
DOI: 10.4143/crt.2018.342
|View full text |Cite
|
Sign up to set email alerts
|

Discordance of the PAM50 Intrinsic Subtypes Compared with Immunohistochemistry-Based Surrogate in Breast Cancer Patients: Potential Implication of Genomic Alterations of Discordance

Abstract: A substantial portion of patients showed discrepancy between IHC subtype and PAM50 intrinsic subtype in our study. The survival analysis demonstrated that current IHC-based classification could mislead the treatment and result in poor outcome. Current guidelines for IHC might be updated accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
52
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 34 publications
6
52
1
1
Order By: Relevance
“…Previous studies have shown significant discordance between clinical subtypes and intrinsic subtypes, which affects the prognosis of BRCA patients. Kim et al reported that discrepancies between the IHC-based subtype and the intrinsic subtype were associated with poor survival, highlighting the limitations of current IHC-based classification methods [30]. Consistent with previous results, we confirmed the poor survival of patients with non-matching subgroup classifications in both the TCGA and METABRIC datasets.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies have shown significant discordance between clinical subtypes and intrinsic subtypes, which affects the prognosis of BRCA patients. Kim et al reported that discrepancies between the IHC-based subtype and the intrinsic subtype were associated with poor survival, highlighting the limitations of current IHC-based classification methods [30]. Consistent with previous results, we confirmed the poor survival of patients with non-matching subgroup classifications in both the TCGA and METABRIC datasets.…”
Section: Discussionsupporting
confidence: 91%
“…This discordance might be due to intratumoral heterogeneity, the coexistence of cells with different subtypes in the same tumor, as well as measurement inaccuracies in subtype profilers, IHC analysis for ER/PR status, and fluorescence in situ hybridization (FISH) analysis for HER2 status. These inconsistencies could result in administration of the wrong treatment, subsequently leading to poor survival [30]. Therefore, accurate identification of receptor status or the intrinsic BRCA subtype is of high clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, cohort 1 was divided into six subtypes based on IHC and ISH. Although it has been shown that surrogate markers can be used for molecular subtyping [24][25][26][27], there is a discrepancy between molecular subtype defined by surrogate markers and subtypes defined by gene expression analyses [28,29]. Nevertheless, similar to Gatza et al, we only found MRPS23 amplified cases among the non-basal tumours.…”
Section: Discussionsupporting
confidence: 59%
“…Veeraraghavan et al found that a clinical subtype in breast cancer with high HER2 amplification and an intact PI3K pathway has a better response to anti-HER2 therapies without chemotherapy [19]. e findings of Kim et al showed that discordance between IHC-based subtypes and PAM50-based intrinsic subtypes was related to inadequate treatment and diminished survival in BC [20]. Studies also indicated that the percentage of stromal tumor-infiltrating lymphocytes (TILs) was associated with a higher pCR rate and improved survival in patients with HER2 + BC [21][22][23].…”
Section: Introductionmentioning
confidence: 99%